Oblicz:
a) -1,5 : 1i 1/8 - 2/9 * ( -3/8)
b) ( 1 i 1/3 * 4 + 0,4 * 2,5 ) * 0,75
c) 1 i 1/3 - 1/25 : 0,04 + 1 i 2/3
d) 1 i 3/20 + 3/4 : 0,6 + 0,2 * (-27)
e) 2,6 + 3,4 : 1,7 + 6/7 * ( -2 i 1/3 )
f) 2,5 * [ 8/15 - (-0,15 ) ] + 5/24
g) 0,15 * 5/6 - ( 0,7 * 3/7 - 4/5 ) : ( - 1 i 1/2 )
h) 0,75 - ( 2 i 1/3 - 1 i 1/9 ) : 4
i) ( 13,3 - 11 i 1/2 ) : 1,8


z góry dzięki ;***

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-14T11:09:40+01:00
A) -1,5 : 1i 1/8 - 2/9 * ( -3/8)=-3/2*8/9 - 2/9* ( -3/8)[skracaamy ułamki]=-4/3+1/12=-8/12+1/12=-7/12

b) ( 1 i 1/3 * 4 + 0,4 * 2,5 ) * 0,75=4/3*4+4/10*25/10=16/3+10/10=16/3+1=6 i 1/3

c) 1 i 1/3 - 1/25 : 0,04 + 1 i 2/3 = 4/3-1/25* 100/4+5/3=4/3-1+5/3=9/3-1=3-1=2

d) 1 i 3/20 + 3/4 : 0,6 + 0,2 * (-27)=23/10+3/4*10/6-54/10= 23/10+5/4-54/10=23/20+25/20-108/20=-60/20=-3

e) 2,6 + 3,4 : 1,7 + 6/7 * ( -2 i 1/3 )=26/10+34/10*10/17+6/7*(-7/3)=26/10+2-2=26/10=2,6
f) 2,5 * [ 8/15 - (-0,15 ) ] + 5/24=25/10*[8/15+3/20]+5/24=25/10*[32/60+6/60]+5/24=25/10* 38/60 +5/24=19/12+ 5/24=38/24+5/24=43/24=1 i 19/24

g) 0,15 * 5/6 - ( 0,7 * 3/7 - 4/5 ) : ( - 1 i 1/2 )=15/100*5/6 - (7/10*3/7 -4/5):(-3/2)=1/6-(3/10-4/5)*(-2/3)=1/6-(3/10-8/10)*(-2/3)=1/6-(- 1/2)*(-2/3)=1/6-1/3=1/6-2/6=-1/6

h) 0,75 - ( 2 i 1/3 - 1 i 1/9 ) : 4 = 3/4-(7/6-10/9)*1/4=3/4-(63/54-60/54)*1/4=3/4-(3/54*1/4)=3/4-(1/18*1/4)=3/4-1/72=54/72-1/72=53/72

i) ( 13,3 - 11 i 1/2 ) : 1,8= (133/10-23/2):18/10=(133/10-115/10)*10/18=18/10*10/18=1